BORROWED WORDS IN ENGLISH AND THEIR TRANSLATION INTO UZBEK: A COMPARATIVE STUDY (Konferensiyalar | Conferences, 2024)
This article provides information about the phenomenon of loan words in the English language, the translation of these words, and the way of usage of these words in communication. The findings unveil important insights into the linguistic and cultural interactions between the two languages, as well as the challenges and reflections involved in the translation process. The study contributes to a broader understanding of language contact, borrowing, and translation practices between English and Uzbek.